Exploring Plasma Coenzyme Q10 Status in Paediatric Dyslipidaemia - Beatriz Minguez; Mariela de Los Santos; Camila Garcia-Volpe; Cristina Molera; Abraham J. Paredes-Fuentes; Clara Oliva; Angela Arias; Helena Rodriguez-Gonzalez; Delia Yubero; Mireia Tondo; Carlos Santos-Ocaña; Silvia Meavilla; et al. (MDPI AG, 2024)
Coenzyme Q10 (CoQ) is a ubiquitous lipid with different biological functions. In blood, there is a close relationship between CoQ status and cholesterol, which strongly supports the study of both molecules simultaneously. The objective of this study was to evaluate plasma CoQ, lipoprotein concentrations and CoQ/Chol ratio in a cohort of paediatric patients with different types of dyslipidaemias. A total of 60 paediatric patients were recruited (age range: 7 months-18 years), including 52 with different types of hypercholesterolemia, 2 with isolated hypertriglyceridemia and 6 with hypobetalipoproteinemia. Plasma CoQ was analysed by HPLC with electrochemical detection, and lipoprotein and cholesterol concentrations by standard automated methods. The lowest CoQ values were detected in patients with hypobetalipoproteinemia and in two cases of liver cirrhosis. Mean CoQ values were significantly higher in hypercholesterolemic patients compared to controls (average values 1.07 µmol/L and 0.63 µmol/L) while the CoQ/cholesterol ratio did not show differences (170 vs. 163, respectively). Mean CoQ values were significantly lower in the group of patients with hypobetalipoproteinemia compared to controls (mean CoQ values of 0.22 µmol/L vs. 0.63 µmol/L, respectively), while those of CoQ/cholesterol did not show differences. Pearson's correlation test showed a positive correlation between the CoQ and cholesterol values (r = 0.565, p < 0.001) and between the CoQ and the LDL cholesterol values (r = 0.610, p < 0.001). Our results suggest that it is advisable to analyse plasma CoQ and cholesterol concentrations in patients with hypobetalipoproteinemia and hypercholesterolemia associated with liver damage.